Adaptive Cyber Law Enforcement Strategies for Combating Digital Crime in Bone Regency - Sandra, Gustika; Jumra, Jumra (Journal of Education, Humaniora and Social Sciences (JEHSS), 2025)
This study examines adaptive cyber law enforcement strategies to address digital crime in Bone Regency, a non-metropolitan area facing regulatory limitations, coordination challenges, and low digital literacy. A qualitative case study approach was employed through interviews with 15 stakeholders, including law enforcement officials, government representatives, legal practitioners, and academics, supplemented with observations and document analysis. The findings reveal four key issues: outdated regulations that do not cover emerging crimes such as deepfakes and encrypted fraud; weak inter-agency coordination caused by slow communication and the absence of standard procedures; limited technical capacity due to a shortage of digital forensic personnel and inadequate infrastructure; and low community awareness that increases vulnerability to cybercrime. Despite these obstacles, adaptive measures were identified, including collaboration with external institutions, local resource mobilization, and community-based education. The study recommends regulatory updates, capacity-building for law enforcement, standardized coordination mechanisms, and inclusive digital literacy programs. These strategies are essential to strengthen cyber law enforcement in non-metropolitan areas and inform policy at both local and national levels.